Final testimonies - Barth, Karl, 1886-1968. (Grand Rapids : Eerdmans, 1977)
Barth's theology is a theology for pastors. Written prior to his death, he reminisces about his political involvements in various causes.
Testimony to Jesus Christ.--Music for a guest, a radio broadcast.--Liberal theology, an interview.--Radio sermons Catholic and evangelical.--Starting out, turning round, confessing.--Epilogue.
Translation of Letzte Zeugnisse.
Keywords: Theology